Harnessing Planting Time: A Strategic Approach to Pest Management Across Diverse Crops - Madhuri, Burjikindi; Bharghavi, Kolli; Maharaj, Satwika; Supriya, Koosari; Erla, Sravanthi; Yashaswini, Gummudala (Chronicle of Bioresource Management, 2020)
The timing of planting, a critical aspect of agricultural practices, emerges as a potent tool in the realm of pest management across various crops. Recognizing the age-old battle between farmers and pests, the study emphasizes the significance of synchronizing planting schedules with insect cycles to enhance crop resilience. By strategically timing plantations, farmers can disrupt key phases in pest life cycles, effectively minimizing vulnerability to infestations. This approach not only avoids invasion during critical periods but also leverages natural enemies and adverse weather conditions to create an unfavourable environment for pests. Additionally, planting time allows crops to mature before pest abundance, compensating for potential damage and reducing the susceptible period of attack. The abstract underscores planting time as a versatile and proactive tool in integrated pest management, fostering sustainable agricultural practices across diverse crop systems.